Microfluidic Microchannel (Size And Shape) for Single Cell Analysis by Numerical Optimization: Lateral Trapping Method - M, Sushmitha; Narayanamurthy, Vigneswaran; James. A, Jasper; Samsuri, Fahmi; N, Padmasini. (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
The primary objective of this work is to show simulation outputs from the developed model of cell flow within a microfluidic device. This work is essential because it requires computational models to offer compact sized biomedical equipment that involves microfluidics technology. Microfluidics has become a common technology for life science applications in latest years. The purpose is to learn the effect of various microchannel size and shape with lateral traps for single cell analysis and to arrive at an optimum design based on a simulation study using COMSOL Multiphysics software. Thus in order to develop software model of various microchannels which execute fluid flow in the microelectronic device. This research provides numerical alternatives from finite element analysissimulation using the software COMSOL-Multiphysics to characterize the shape and size of the microchannel initializing the fluid flow. Optimized design analysis and operating conditions for efficient single cell trap is reported.